2021
DOI: 10.26719/emhj.21.042
|View full text |Cite
|
Sign up to set email alerts
|

Primary health care reform in Saudi Arabia: progress, challenges and prospects

Abstract: Background: Saudi Arabia embarked on transforming its primary health care system in 2016 to meet international standards, gain the people’s trust and respond to the growing burden of noncommunicable diseases, as proposed in the Saudi Vision 2030. Aims: This review aims to highlight the progress, identify challenges and prospects for Saudi Arabia’s PHC reform process in order to make recommendations to facilitate strengthening of the PHC system. Methods: A review of previous studies and governmental reports was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 8 publications
2
45
0
Order By: Relevance
“…(2021) about the crucial role and responsibility of the primary health care physicians in modifying parental perception about childhood obesity. [ 19 ] The current study showed that the percentage of parents who had correct perception about the weight status of their children was significantly lowest among the parents of preschool children than older children, which could be attributed to what had been stated by Almoosawi et al . [ 12 ] who argued that the parents of toddlers and young children “might not consider their child to be overweight because he/she engages in physical activity, and they are not teased about his/her size, as long as there are no obvious health issues.” This argument was emphasized later by Ruiter et al .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…(2021) about the crucial role and responsibility of the primary health care physicians in modifying parental perception about childhood obesity. [ 19 ] The current study showed that the percentage of parents who had correct perception about the weight status of their children was significantly lowest among the parents of preschool children than older children, which could be attributed to what had been stated by Almoosawi et al . [ 12 ] who argued that the parents of toddlers and young children “might not consider their child to be overweight because he/she engages in physical activity, and they are not teased about his/her size, as long as there are no obvious health issues.” This argument was emphasized later by Ruiter et al .…”
Section: Discussionsupporting
confidence: 71%
“…[ 18 ] In this regard, Al Khashan et al . (2021)[ 19 ] asserted that primary health care physicians, being in the front line of health systems, are responsible for early detection of childhood obesity and increasing awareness of parents about the risks of obesity and how to prevent it.…”
Section: Introductionmentioning
confidence: 99%
“…As of December 2021, the number of PHC centers within the Kingdom of Saudi Arabia (KSA) was 2,121, 63 of which are in the Al-Ahsa region [ 15 ]. With the ongoing PHC reform plans, easier access to care including teleconsultation services through a toll-free number (937) as well as the SEHA Ministry of Health application, 6,500 and 1,500 daily teleconsultations are being offered, respectively [ 16 ]. These major reform plans are continuously evolving to meet the overgrowing expectations of the citizens.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of public service reform is still experiencing obstacles, especially related to human resources, [1][2][3][4] including reforms in the autonomy of PHC in Indonesia, otherwise called RPSAPHC, 7 which were authorized for SFM. In this cross-sectional study, 29 PLS-SEMs were used to examine the suitability of the model of autonomous self-finance management in PHC to enhance workers' satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…This concept has shown improvement; however, public service reform still faces obstacles toward transformation processes; these obstacles are mainly related to human resources. [1][2][3][4] Human resources need to be considered as they play an important role in the success of operational management to achieve organizational goals. A previous study showed that threequarter of the respondents were dissatisfied with their working conditions.…”
Section: Introductionmentioning
confidence: 99%